Nanoscale biomimetics studies of Salvinia molesta for micropattern fabrication - Hunt, James; Bhushan, Bharat (Journal of colloid and interface science, 2011)
Water droplet suspended by Salvinia molesta hair at horizontal and vertical orientations demonstrating air pocket formation and water pinning. In this study, a novel methodology for the fabrication of microstructures that mimic the water-pinning and air-trapping ability of S. molesta was introduced. [Display omitted] ► The air-trapping and water-pinning abilities of Salvinia molesta were investigated. ► Micropatterns mimicking behavior of S. molesta were created. ► Novel micropattern fabrication techniques were introduced. ► Adhesion of S. molesta and micropatterns were investigated. The emerging field of biomimetics allows one to take inspiration from nature and mimic it in order to create various products, devices and structures. There are a large number of objects, including bacteria, plants, land and aquatic animals and seashells, with properties of commercial interest. The subject of interest for this research is the water fern Salvinia molesta because of its ability to trap air. Air-retaining surfaces are of technological interest due to their ability to reduce drag when used for fluid transport, ship coatings and other submersible industrial products in which drag is a concern. The purpose of this research is to mimic the air trapping ability of S. molesta in order to prove that a structure can be created in the lab that can mimic the behavior of the fern as well as demonstrate microfabrication techniques that can be utilized in industry to produce such materials. In this work, a novel methodology for the fabrication of microstructures that mimic the water-pinning and air-trapping ability of S. molesta is introduced. Water contact angle, water roll angle and adhesive force of the new microstructure and water fern are investigated.